Letter : Food for Spain (potatoes) - Schevenels, Walther, b. 1894
032-0083-001 INTERNATIONAL FEDERATION OF TRADE UNIONS 9, Avenue d'Orsay, Paris-VIIe Sch/T Your Reference: HVT"AC/147 TELEGRAMS: INTERFED—PARIS TELEPHONE: INVALIDES 45-88 AFFILIATED COUNTRIES: ARGENTINE AUSTRIA BELGIUM CANADA CZECHOSLOVAKIA DANTZIG DENMARK DUTCH EAST INDIES ESTONIA FINLAND FRANCE GREAT BRITAIN GREECE HOLLAND HUNGARY INDIA LUXEMBURG MEMEL TERRITORY PALESTINE POLAND ROUMANIA SOUTH AFRICA SOUTH-WEST AFRICA SPAIN SWEDEN SWITZERLAND YUGOSLAVIA EXECUTIVE COMMITTEE: President W. M. Citrine, Great Britain; Vice-Presidents: H. Jacobsen, Denmark; L. Jouhaux, France; E. Kupers, Holland; Corn. Mertens, Belgium; R. Tayerle, Czechoslovakia; General Secretary: W. Schevenels. Letter: F. I. de Sol. No. 508 17th March, 1939. Mr. H.V. Tewson, Trade Union Congress, Transport House, Smith Square, London, S.W.1. Dear Comrade Tewson, Food for Spain, (Potatoes). With reference to your letter of the 14th March the thirty-three tons of potatoes sent from Garston to Cerbere were seized by the military authorities as they believed they belonged to the Government. After we had made representations the military authorities recognised that they had made a mistake, and are now willing to pay for the value of the goods. It was for this reason that we asked for the purchase price of the potatoes, and we should also find it very useful if we could have the invoice for the goods, so that when payment is made we may have evidence to show that we are the owners. We are still sending food to Central Spain and if you should send any more, the consignments should be addressed to Ginesta et Cie, 1 Rue de la Republique, Marseilles, for the order of F.I.S., Jose Castro, Bon Repos, Valencia. I am taking this opportunity of thanking you for your other letter of the 14th March, enclosing a cheque for £1,000 for the assistance of the Central Fund, the official receipt for which I am enclosing. Yours sincerely, W. Schevenels. General Secretary. Enclosure. 292/946/32/83